2017
DOI: 10.1371/journal.pone.0185867
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure in the southernmost populations of black-and-gold howler monkeys (Alouatta caraya) and its conservation implications

Abstract: Black-and-gold howler monkeys Alouatta caraya, are arboreal primates, inhabitants of Neotropical forests, highly susceptible to the yellow fever virus, considered early 'sentinels' of outbreaks, and thus, of major epidemiological importance. Currently, anthropogenic habitat loss and modifications threatens their survival. Habitat modification can prevent, reduce or change dispersal behavior, which, in turn, may influence patterns of gene flow. We explored past and contemporary levels of genetic diversity, eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 67 publications
2
43
0
4
Order By: Relevance
“…This is the only site where howler monkey roars need to travel through open grasslands to reach groups inhabiting other forest patches, 2—Parque Nacional Chaco (PN Chaco, 26°48′S; 59°36′W), a riverine forest along the Negro River, 3—Reserva privada Guaycolec (Guaycolec 25°54′S; 58°13′W), a tall and dense riverine forest along the Pilagá River, and 4—Reserva de Vida Silvestre Yacutinga (Yacutinga 25°35′S; 54°03′W), a typical dense and closed subtropical forest. The genetic structure of the four A. caraya study populations demonstrated three genetically differentiated clusters: (K1) EBCo, (K2) PN Chaco and Guaycolec, and (K3) Yacutinga (Oklander et al, ; Figure b).…”
Section: Methodsmentioning
confidence: 96%
See 4 more Smart Citations
“…This is the only site where howler monkey roars need to travel through open grasslands to reach groups inhabiting other forest patches, 2—Parque Nacional Chaco (PN Chaco, 26°48′S; 59°36′W), a riverine forest along the Negro River, 3—Reserva privada Guaycolec (Guaycolec 25°54′S; 58°13′W), a tall and dense riverine forest along the Pilagá River, and 4—Reserva de Vida Silvestre Yacutinga (Yacutinga 25°35′S; 54°03′W), a typical dense and closed subtropical forest. The genetic structure of the four A. caraya study populations demonstrated three genetically differentiated clusters: (K1) EBCo, (K2) PN Chaco and Guaycolec, and (K3) Yacutinga (Oklander et al, ; Figure b).…”
Section: Methodsmentioning
confidence: 96%
“…Sampled populations are separated with white dashed lines. Equally color populations share genetic ancestry (modified from Oklander et al ) [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations